2019
DOI: 10.1002/pa.2031
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of agriculture in economic growth: A case study of West Bengal (India)

Abstract: Economists have argued that role of agriculture is pivotal for economic development of the nation. Worldwide studies have shown that agriculture sector is more effective in reducing hunger and poverty than other sectors. This study is an attempt to ascertain the importance of agriculture in the economic growth of West Bengal. Agriculture, being the source of livelihood and supplier of raw material to various industries, triggers economic growth of the nation. This paper exhibits how agriculture has contributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 11 publications
1
17
0
2
Order By: Relevance
“…In order for this change to happen, education, engineering and many branches of science are also needed besides agriculture. This assessment is supported by other studies (Aydogan & Vardar, 2020; Khan et al, 2020). At the same time, this change will enable agriculture to play an important role in exports, as in another study with similar findings (Hwa, 1988;Dawson, 2005;Michler, 2020) The limitations of this study measure the discussion about the role of agriculture in promoting economic growth in selected countries with the variables used in the model.…”
Section: Discussionsupporting
confidence: 81%
“…In order for this change to happen, education, engineering and many branches of science are also needed besides agriculture. This assessment is supported by other studies (Aydogan & Vardar, 2020; Khan et al, 2020). At the same time, this change will enable agriculture to play an important role in exports, as in another study with similar findings (Hwa, 1988;Dawson, 2005;Michler, 2020) The limitations of this study measure the discussion about the role of agriculture in promoting economic growth in selected countries with the variables used in the model.…”
Section: Discussionsupporting
confidence: 81%
“…The contribution of agricultural productivity to economic growth is strongly significant. Efforts to increase labor productivity in agriculture provide more labor input for the industrial sector while also creating an increase in demand for agricultural machinery and equipment produced by the industrial sector (Khan et al, 2020). It also increases foreign exchange earnings via rising agricultural exports.…”
Section: Resultsmentioning
confidence: 99%
“…They came to the same conclusion as Oyakhilomen and Zibah (2014). In their recent study, Khan et al (2020) found that the agricultural sector positively impacts other sectors' economic growth in West Bengal. They concluded a long-run causality between the agricultural and industrial sectors, the service sector, and overall economic growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Global studies have revealed that agriculture division is more effective in reducing hunger and poverty than other sectors. [16] In [17] demonstrate that the number of traditional small farms strongly declines, being replaced by modern and larger farms. In [18] they instructed that agriculture is undergoing a fourth revolution triggered by the exponentially increasing use of knowledge and communication technology (ICT) in agriculture.…”
Section: Introductionmentioning
confidence: 99%